Peran Lembaga Pemasyarakatan Dalam Menanggulangi Kekerasan Yang Dilakukan Sesama Narapidana Di Lembaga Pemasyarakatan Kelas II A Kupang - Ludji, Selvia Enjelita; Amalo, Heryanto; Manafe, Deddy R. CH. (Law Faculty, Nusa Cendana University, 2025)
Criminals with various backgrounds and levels of violent crime are in the same place, which causes the coaching process to not run as expected. Prison sentences have not been able to deter perpetrators of violent crimes. This can be proven by the increasing number of violent crimes that occur in prison environments. Activities in correctional institutions are not just to punish or guard prisoners but include a coaching process so that inmates realize their mistakes and improve themselves and do not repeat the crimes they have committed. The main problems of this research are (1) What are the factors causing violence between inmates in Class II A Kupang Penitentiary? (2) What is the role of the Penitentiary in overcoming violence between inmates in Class II A Kupang Penitentiary?. This type of research is Empirical legal research. The approach in this study is a qualitative descriptive approach. The location of the research that the author took was the Class II A Kupang Correctional Institution. The sources and types of data used are primary data and secondary data. Data collection techniques use interview techniques and literature studies. Data management and analysis in this study use qualitative descriptive analysis.